Matharpacady-03.jpg - Mumbai Archive Project Team (Jio Institute, 2024)
The region around Matharpacady was renowned for mango groves and paddy fields. As mentioned in the book “Bombay: The Cities Within”, in 1749, a portion of the paddy fields west of Mazagaon was leased to DN Rustamji and Dhanji Punja. Over time they came to be known as mhatre, meaning ‘respected elder’ in Marathi, thus the neighbourhood came to be known as Matharpacady, meaning “quarter of the elders”. The mango groves are now long gone but the green cover has survived in some parts.